2000
DOI: 10.1007/pl00007894
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hyaluronan by normal and wounded rabbit iris

Abstract: Our findings demonstrate synthesis of hyaluronan by normal and traumatized iris. The iris seems to be the most important source of aqueous hyaluronan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…When cultured chick embryo fibroblasts are appropriately stimulated, extracellular hyaluronan reaches a 1.9‐fold accumulation in 6 hours and a 3.9‐fold accumulation in 10 hours (Moscatelli & Rubin 1977). Besides, in another study, hyaluronan synthesis has in iris been demonstrated both in vivo and in organ culture in normal and traumatized eyes (Koralewska‐Makár et al 2000). Thus the iris seems to be the site for hyaluronan production after laser irradiation and probably the most important source of the increased aqueous hyaluronan induced by the laser treatment.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…When cultured chick embryo fibroblasts are appropriately stimulated, extracellular hyaluronan reaches a 1.9‐fold accumulation in 6 hours and a 3.9‐fold accumulation in 10 hours (Moscatelli & Rubin 1977). Besides, in another study, hyaluronan synthesis has in iris been demonstrated both in vivo and in organ culture in normal and traumatized eyes (Koralewska‐Makár et al 2000). Thus the iris seems to be the site for hyaluronan production after laser irradiation and probably the most important source of the increased aqueous hyaluronan induced by the laser treatment.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously shown that hyaluronan concentrations increase in iris tissue and in aqueous humor after surgical trauma (Koralewska‐Makár et al 2000, 1998). However, we previously used an iridectomy as our standard iris trauma, and then inevitably also induced corneal trauma in the form of a surgical incision and a suture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes in aqueous hyaluronan concentration corresponded to similar changes in the iris. In another study, we were able to demonstrate in situ production of hyaluronan by normal and wounded iris tissue in vivo as well as in culture (Koralewska‐Makár et al. 2000).…”
mentioning
confidence: 97%